2019
DOI: 10.1001/jamanetworkopen.2019.17126
|View full text |Cite
|
Sign up to set email alerts
|

Association of Longitudinal Changes in Cerebrospinal Fluid Total Tau and Phosphorylated Tau 181 and Brain Atrophy With Disease Progression in Patients With Alzheimer Disease

Abstract: IMPORTANCE The amyloid/tau/neurodegeneration (A/T/N) framework uses cerebrospinal fluid (CSF) levels of total tau (tTau) as a marker of neurodegeneration and CSF levels of phosphorylated tau 181 (pTau181) as a marker of tau tangles. However, it is unclear whether CSF levels of tTau and pTau181 have similar or different trajectories over the course of Alzheimer disease. OBJECTIVES To examine the rates of change in CSF levels of tTau and pTau181 across the Alzheimer disease course and how the rates of change are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
8
22
0
Order By: Relevance
“…The current findings between plasma pTau181 and brain atrophy corroborate previous research on CSF and plasma pTau181 [ 6 , 28 ]. Higher levels of phosphorylated tau predicted neurodegeneration in the medial temporal and periventricular WM among other regions in aging and AD [ 28 , 29 ]. In CI individuals, plasma pTau181 was correlated with degeneration of GM in the precuneus and temporal lobes [ 6 ].…”
Section: Discussionsupporting
confidence: 91%
“…The current findings between plasma pTau181 and brain atrophy corroborate previous research on CSF and plasma pTau181 [ 6 , 28 ]. Higher levels of phosphorylated tau predicted neurodegeneration in the medial temporal and periventricular WM among other regions in aging and AD [ 28 , 29 ]. In CI individuals, plasma pTau181 was correlated with degeneration of GM in the precuneus and temporal lobes [ 6 ].…”
Section: Discussionsupporting
confidence: 91%
“…CSF and blood-based biomarkers reflect properties of the brain and body at the time of collection. Prior work suggested that CSF biomarkers of neuronal injury decline at symptomatic stages of AD ( Llibre-Guerra et al, 2019 ; Sutphen et al, 2018 ), which could lead to a mismatch between biofluid and imaging markers in later stages of disease. Further work is needed to test whether the relationship between imaging and NfL measures changes at more advanced stages of neurodegenerative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the differential diagnosis of dementia is largely based on the symptom spectrum of patients. Recent progress in molecular imaging (Janelidze et al, 2020 ; Kantarci et al, 2020 ; Kozlova et al, 2020 ) and cerebrospinal fluid (CSF) biomarkers (Altomare et al, 2019 ; Llibre-Guerra et al, 2019 ) improved the diagnostic accuracy of dementia. However, due to the high cost and invasiveness of these diagnostic strategies, blood-based biomarkers are in urgent need for the diagnosis and differential diagnosis of dementia.…”
Section: Discussionmentioning
confidence: 99%